2010
DOI: 10.1029/2009jd012745
|View full text |Cite
|
Sign up to set email alerts
|

Impact of East Asian summer monsoon on the air quality over China: View from space

Abstract: are analyzed using the Regional Chemical and Transport Model to investigate the impact of the East Asian summer monsoon on the air quality over China. The observed and simulated migrations of O 3 and CO are in good agreement, demonstrating that the summer monsoon significantly affects the air quality over southeastern China, and this influence extends to central East China from June to July. Enhancements of CO and O 3 over southeastern China disappear after the onset of the summer monsoon and reemerge in Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 70 publications
(95 reference statements)
4
102
0
Order By: Relevance
“…Moreover, Zhang et al (2010) used a numerical model to simulate the impact of weak/strong monsoon circulations on interannual variations of aerosols over eastern China under the conditions of the same anthropogenic emissions and suggested that the decadal-scale weakening of the East Asian summer monsoon is responsible for the increase in aerosol concentrations over eastern China. Using satellite products, Zhao et al (2010) showed consistent disappearance of CO and ozone (O 3 ) enhancements over southeastern China at the onset of East Asian summer monsoon and the reemergence after the monsoon wanes, which confirmed the strong modulation of monsoon system on regional air quality. Liu et al (2013) further demonstrated a potential influence from the variation of large-scale circulation, El Niño-Southern Oscillation, upon the interannual fluctuation of summertime aerosol optical depth (AOD).…”
Section: Y Zheng Et Al: Impact Of Atmospheric Circulations On Aementioning
confidence: 67%
“…Moreover, Zhang et al (2010) used a numerical model to simulate the impact of weak/strong monsoon circulations on interannual variations of aerosols over eastern China under the conditions of the same anthropogenic emissions and suggested that the decadal-scale weakening of the East Asian summer monsoon is responsible for the increase in aerosol concentrations over eastern China. Using satellite products, Zhao et al (2010) showed consistent disappearance of CO and ozone (O 3 ) enhancements over southeastern China at the onset of East Asian summer monsoon and the reemergence after the monsoon wanes, which confirmed the strong modulation of monsoon system on regional air quality. Liu et al (2013) further demonstrated a potential influence from the variation of large-scale circulation, El Niño-Southern Oscillation, upon the interannual fluctuation of summertime aerosol optical depth (AOD).…”
Section: Y Zheng Et Al: Impact Of Atmospheric Circulations On Aementioning
confidence: 67%
“…2 A and B). We simulate the Octobers of 2008-2010 by using the Regional chEmical trAnsport Model (REAM) (24,25) to examine the key parameters driving the surface ozone difference among the three years. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used the 3D REAM to explore the missing mechanisms in the biosphere-chemistry-climate interactions. The REAM has been applied over North America, East Asia, and the Polar Regions (24,25,(44)(45)(46)(47)(48)(49). The model has a horizontal resolution of 36 km and 30 vertical layers in the troposphere.…”
Section: Methodsmentioning
confidence: 99%
“…He et al (2008) analyzed the seasonal variations of O 3 concentrations measured over the period [2004][2005][2006] and found that O 3 concentrations peak in spring and autumn with a summer trough in central eastern China and the western Pacific, the areas that are influenced by clean air from the southern oceans during the summer monsoon. Studies by , Lin et al (2009), and Zhao et al (2010) reported that the increasing clouds associated with the EASM rainfall suppress photochemical production of O 3 by altering solar radiation, which also contributes to the minimum O 3 concentrations in summer.…”
Section: H Liao Et Al: Interannual Variations Of Summertime Surfacementioning
confidence: 99%